If A = 3x² - 4x + 1, B = 5x² + 3x - 8 and C = 4x² - 7x + 3, then find B + C - A
Solution:
Given, A = 3x² - 4x + 1, B = 5x² + 3x - 8 and C = 4x² - 7x + 3
We have to find B + C - A
C - A = 4x² - 7x + 3 - (3x² - 4x + 1)
= 4x² - 7x + 3 - 3x² + 4x - 1
By combining like terms,
= 4x² - 3x² - 7x + 4x + 3 - 1
= (4 - 3)x² + (-7 + 4)x + (3 - 1)
= (1)x² + (-3)x + 2
C - A = x² - 3x + 2
Now, B + C - A = 5x² + 3x - 8 + (x² - 3x + 2)
= 5x² + 3x - 8 + x² - 3x + 2
By combining like terms,
= 5x² + x² + 3x - 3x - 8 + 2
= (5 + 1)x² + (3 - 3)x + (-8 + 2)
= (6)x² + (0)x + (-6)
Therefore, B + C - A = 6x² - 6
✦ Try This: If A = x² + x + 1, B = 4x² - 3x + 2 and C = x² - 4x + 6, then find B + C - A
☛ Also Check: NCERT Solutions for Class 7 Maths Chapter 12
NCERT Exemplar Class 7 Maths Chapter 10 Problem 68 (ii)
If A = 3x² - 4x + 1, B = 5x² + 3x - 8 and C = 4x² - 7x + 3, then find B + C - A
Summary:
If A = 3x² - 4x + 1, B = 5x² + 3x - 8 and C = 4x² - 7x + 3, then B + C - A is 6x² - 6
☛ Related Questions:
visual curriculum